Estimation of the Effect of External Information on Participants of Web- Communities by IT-Tools under Conditions of Behavioral Economy - Kravchenko Olga V.; Danchenko Elena B.; Bedrii D. I.; Marunych V. S. (Problems of the Regional Energetics)
The issues concerning the decision making by a person under the effect of the external information are considered. The authors classify the directions of the existing research. The aim of the study is to analyze the degree of the effect of the external information on a participant of the web-community when making a decision. The aim was achieved with the help of the developed system for collecting and analyzing information in accordance with the rules of the behavioral economics. For the collection and throwing of the necessary information the bot is responsible. The authors expanded and introduced such concepts as: "participant of the web-community", "price of opportunity"," HindSight bias", "expected utility", "utility graph" for the IT sphere. A mathematical model based on the method of analogies of interphase interaction problems is constructed. The structure of the data analysis system of the participants of the web-societies is described with the help of which the collection and processing of data takes place. A useful utility graph is constructed. The most important result in assessing the influence of the external information on the formation of the member’ own decision of the web community is that the average value of interest support under the influence of the negative information, from the viewpoint of the subject, increased insignificantly, whereas under the influence of the positive information it has grown substantially. The significance of the results was that the approach developed by the authors can be the basis for construction of new models and methods for forecasting the result of the effect of the external information.